The memory of Ignatius of Antioch the Martyr as a locus of Christian identity, remembering and remembered - MacDiarmid, Frazer 1993-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
In diesem Band zeigt Frazer MacDiarmid, wie »Erinnerung« einen Interpretationsschlüssel liefert, um Ignatius von Antiochien zu erschließen. Der Autor weist nach, dass das reiche literarische Erbe des Ignatius den Märtyrer gleichzeitig als jemanden zeigt, der sich erinnert, der danach strebt, wahrer Erinnerung würdig zu sein, und als jemanden, an den sich tatsächlich erinnert wird.InhaltsübersichtPart I: The Remembering IgnatiusChapter 1: Patriarchs, Prophets and Israel: Remembered and ReconstructedChapter 2: Ignatius' Inheritance of 'Extra-Christian' MemoryPart II: Memory Poiesis' – Ignatius as a Forger of his own Memorialisation Chapter 3: θυσία θεοῦ: Ignatius' Self-Construction as SacrificeChapter 4: The Girardian IgnatiusPart III: The Early Christian Memory of IgnatiusChapter 5: Authenticity and Forgery in Literary RemembranceChapter 6: Ignatius in the Long RecensionChapter 7: The Ignatian Cult: Martyrology and Material Culture
The concept of 'memory' provides remarkable insight into the early second-century bishop and martyr Ignatius of Antioch. In this work, Frazer MacDiarmid seeks to explore the nature of this insight and unpack its significance. Ignatius' rich literary legacy and personal preoccupation with remembering make him uniquely suited among early Christians to be unlocked by the key of memory. As is becoming increasingly recognised, remembering in community is central to the development of the early church, its theology and self-understanding. This volume is structured around three related questions: What is the nature of the memories inherited by Ignatius and his communities, and how are they engaged in the rhetorical and polemical context of his letters? How does Ignatius construct himself as a figure to be remembered by Christian interpreters? And how was Ignatius in fact memorialised in early Christian history?Survey of contentsPart I: The Remembering IgnatiusChapter 1: Patriarchs, Prophets and Israel: Remembered and ReconstructedChapter 2: Ignatius' Inheritance of 'Extra-Christian' MemoryPart II: Memory Poiesis' – Ignatius as a Forger of his own Memorialisation Chapter 3: θυσία θεοῦ: Ignatius' Self-Construction as SacrificeChapter 4: The Girardian IgnatiusPart III: The Early Christian Memory of IgnatiusChapter 5: Authenticity and Forgery in Literary RemembranceChapter 6: Ignatius in the Long RecensionChapter 7: The Ignatian Cult: Martyrology and Material Culture
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe; Versammlungsgeschichte; gebundene Verwaltung; René Girard; Persecution; Martyrdom; Martyrology; Forgery/pseudepigraphy; Neues Testament; Kirchengeschichte; Array; Dekolonisation; Hochschulschrift